History of the british iron and steel industry : - Schubert, H. R. (Routledge and Kegan Paul, 1957)
Will be shipped from US. Used books may not include companion materials, may have some shelf wear, may contain highlighting/notes, may not include CDs or access codes. 100% money back guarantee.